Examination of Separate and Mixed Reﬁ ning Methods on Softwood and Hardwood Pulps for Linerboard Production - Panthai , Supattra; Somboon, Phichit (Agriculture and Natural Resources, 2014)
The research focused on the study of process modiﬁ cation of chemical pulp reﬁ ning for a mixed treatment and separate methods for softwood and hardwood pulps in the production of linerboard. The study had the objectives to examine the effect of treatments on pulp quality, to ﬁ nd out the optimum levels of pulp development and to examine their reﬁ ning efﬁ ciency. This study was carried out using a laboratory Valley beater and the pulp materials were obtained from linerboard manufacturers. The results showed that the separate and mixed reﬁ ning methods produced different qualities of the ﬁ nal blended pulp. In separate reﬁ ning, the softwood pulp needed to be reﬁ ned to a freeness of 500 mL and the hardwood pulp was required to be reﬁ ned to a freeness of 320 mL, to obtain a superior strength of laboratory sheets. The wrong treatment of softwood and hardwood pulps produced severe degradation of the sheet quality. The treatment efﬁ ciency using the laboratory device was not clearly differentiated between the methods. The results from the study could be applied to industrial reﬁ ning as criteria to control the reﬁ ning levels of pulp materials in separate reﬁ ning, while the energy efﬁ ciency could be further studied using a pilot reﬁner.